Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.pone.0087712
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Innate Receptors with MIS416 Reshapes Th Responses and Suppresses CNS Disease in a Mouse Model of Multiple Sclerosis

Abstract: Modification of the innate immune cell environment has recently been recognized as a viable treatment strategy for reducing autoimmune disease pathology. MIS416 is a microparticulate immune response modifier that targets myeloid cells, activating cytosolic receptors NOD2 and TLR9, and has completed a phase 1b/2a trial for the treatment of secondary progressive multiple sclerosis. Using a mouse model of multiple sclerosis, we are investigating the pathways by which activation of TLR9 and NOD2 may modify the inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 51 publications
6
70
2
Order By: Relevance
“…There was an intermediate reduction in the spleen, an untreated site – likely due to non-specific, systemic effects of Rapa. Supporting this hypothesis, recent literature demonstrates that systemic treatments with modulatory or suppressive drugs can cause differential impacts on inflammatory responses in different tissues – findings that also illustrate the utility of having a tool to directly probe how signals in one tissue impact the course, efficiency, and durability of tolerance (White et al, 2014). One further rationale for co-delivery of tolerogenic signals (e.g., Rapa) with self-antigen is to mitigate the risk of exacerbating disease with a therapy containing disease-relevant antigen during active autoimmunity (Maldonado et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…There was an intermediate reduction in the spleen, an untreated site – likely due to non-specific, systemic effects of Rapa. Supporting this hypothesis, recent literature demonstrates that systemic treatments with modulatory or suppressive drugs can cause differential impacts on inflammatory responses in different tissues – findings that also illustrate the utility of having a tool to directly probe how signals in one tissue impact the course, efficiency, and durability of tolerance (White et al, 2014). One further rationale for co-delivery of tolerogenic signals (e.g., Rapa) with self-antigen is to mitigate the risk of exacerbating disease with a therapy containing disease-relevant antigen during active autoimmunity (Maldonado et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…MIS416 has been suggested to modulate T-cell-mediated autoimmune responses in EAE by simultaneously activating innate Toll-like receptor 9 and nucleotide-binding oligomerization domain-containing protein 2 [96]. The restricted uptake of MIS416 by phagocytic cells has been suggested to lead to targeted modulation of the innate immune system [97]. MIS416 was initially used in patients with SPMS outside of a formal clinical trial setting under compassionate use legislation in New Zealand.…”
Section: Mis416mentioning
confidence: 99%
“…MIS416 was initially used in patients with SPMS outside of a formal clinical trial setting under compassionate use legislation in New Zealand. Recently, in a phase Ib/IIa clinical trial, MIS416 was shown to suppress the development of proinflammatory T helper (Th)1, Th2, and Th17 cells in EAE, and to i ncrease the serum level s of IFN-γ and IFN-γ-associated proteins in 19 patients with SPMS [97]. A phase IIb trial is underway to further investigate the effect of MIS416 in progressive forms of MS (NCT02228213) [98].…”
Section: Mis416mentioning
confidence: 99%
“…In experimental animal models, the partial blockade of sodium channels showed neuroprotective properties [87,88,89]. …”
Section: Therapeutic Advances and Future Prospects In Progressive mentioning
confidence: 99%